PERCEPTION OF MIDDLE MANAGER ON FACTORS AFFECTING THE SUCCESS OF TOTAL QUALITY MANAGEMENT (TQM) IMPLEMENTATION IN CITY HALL: A CASE STUDY IN KOTA KINABAL U CITY HALL, SABAH - Chong, Vun Le (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Generally, the aim of this study is to identify the middle manager's perception towards the factors affecting the success of Total Quality Management (TQM) implementation in Dewan Bandaraya Kota Kinabalu, Sabah. The objectives of this study are to determine the relationship between perceptions of middle manager towards the factors that influence the TQM implementation such as leadership, training, communication and top management support. This study also aims to identify the success of TQM implementation in DBKK and the level of respondent 's perception. Questionnaires were used to obtain the data for this study. All the middle manager had been selected to be the sample of this study. There are 37 middle managers from a total population of 50. Data collected was analyzed by using SPSS (Statistical Package for Social Sciences), version 11.0. Ttest shows that there is no significant difference between the middle manager 's perceptions on gender (t=0904) towards the success of TQM implementation. ANOVA shows that there is no significant difference between the middle manager's perceptions on education level (F=0.147) and year of services (F=1.687) towards the success of TQM implementation. Pearson correlation test shoii's that there is a significant correlation between the middle manager 's perceptions on training (r=0.631), leadership (r=0.343), communication (r=0.598) and top management support (r=0.503) towards the success of TQM implementation. Finally, multiple regression analysis was found that training was the most dominant factor influencing the success of TQM implementation and have contributed 35.7% out of the overall. factors. In conclusion, the organization should provide more training programme to the employees. Top management and middle manager should clearly understand their oi, 'n role in leadership and communication to ensure that all the activities of TQM would be implemented effectively by employees. Support such as encouragement and motivation should be given to the employees. In conjunction. the . findings Jroiii this study may provide useful guidelines fin- the organization in improving the success of TQA> implementation in the organization.